A content analysis of the consumer-facing online information about My Health Record: Implications for increasing knowledge and awareness to facilitate uptake and use. Issue 3 (September 2018) - Walsh, Louisa; Hill, Sophie; Allan, Meredith; Balandin, Susan; Georgiou, Andrew; Higgins, Isabel; Kraal, Ben; McCarthy, Shaun; Hemsley, Bronwyn
Background: Low health literacy, low levels of positive belief and privacy and security concerns have been identified as a significant barrier to personal electronic health record uptake and use. An important tool for overcoming these barriers is the consumer-facing information which accompanies the system. My Health Record (MyHR) is the Australian national e-health record system, for which a large suite of online resources exists to facilitate consumer registration and use. This study uses a number of different measures of health resource quality to assess the MyHR online consumer-facing information and identify any gaps or areas for improvement. Objective: To analyse the quality and content of the online consumer-facing resources which support the uptake and use of MyHR. Method: Australian information resources aimed at healthcare consumers about the MyHR were included in this study. A comprehensive search using Internet search engines was conducted to locate all online consumer-facing resources about MyHR from both government and non-government sources. Readability (measured by Flesch–Kincaid grade level), year of publication/review, publishing organisation type, presentation style, linked websites, target audience, and themes were identified as important measures of health information quality, and these were recorded and reported on for each resource. Results: Eighty resources met the inclusion criteria. The mean Flesch–Kincaid grade level was 11.8. Most resources were created by Australian government sources ( n = 55), and the most common target audience was the general public ( n = 65). Registration ( n = 51), privacy/security ( n = 49), and benefits of use ( n = 46) were the most common resource themes. Conclusion: The authors identified a number of gaps and areas for improvement in the provision of consumer-facing information about MyHR. Readability is too high for the general Australian population, and there are few translated resources, which means that the information provided does not cater to people with low literacy levels, communication disability, and/or difficulties in understanding written English. The target audiences for resources do not reflect priority groups that were identified during the MyHR development processes. There are also gaps in information provision about how consumers can use MyHR as a tool to meaningfully engage with health professionals and services to support their own person-centred care.